Bibliometric Using Vosviewer with Publish or Perish (using Google Scholar data): From Step-by-step Processing for Users to the Practical Examples in the Analysis of Digital Learning Articles in Pre and Post Covid-19 Pandemic - Dwi Fitria Al Husaeni; Asep Bayu Dani Nandiyanto (Universitas Pendidikan Indonesia (UPI), 2022)
The purpose of this study is to analyze and demonstrate step-by-step bibliometric data analysis using VOSViewer completely and systematically. Step-by-step analysis was provided to make first-time users easily following the way how to use VOSviewers. This report allows and provides an easy way of data analysis by utilizing mapping tools and provide analysis of research developments regarding digital learning media. The method used in this research is to perform bibliometric analysis to produce network visualization of co-work maps and density maps of co-works. The analysis was carried out with the number of publications obtained, relating to the predetermined topics totaling 88 documents in 2017-2021. As practical examples, we evaluated the analysis of digital learning articles in pre and post covid. We found that VOSviewer can be used to give suggestions in the data analysis results.